Implementasi Model Pembelajaran Numbered Head Together (NHT) Pada Materi Magnet Kelas VI MI Nurul Ulum Sidomukti - Mu’tiqoh Izzatun Nadiyah (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The purpose of this research is to describe how an implementation of the Numbered Head Together (NHT) learning model in the magnetic material procedure for students in class VI MI. Nurul Ulum Sidomukti. Research being carried out at this time uses the library method where the method originates from journals, books, or others. The subjects used in the study were students of class VI MI. Nurul Ulum Sidomukti, totaling 25 students. The analysis used in this research is using content analysis where the analysis is carried out by an in-depth study that is related to the content of written and printed news in the media. The results of this study revealed that the Numbered Head Together learning model in class VI MI magnetic materials. Nurul Ulum Sidomukti has been running quite well and has experienced an increase in understanding of learning material. This activity is carried out because there is an implementation in learning, namely there are four stages in the Numbered Head Together learning model including numbering, asking a question, thinking in groups, and sharing answers.